Environmental law from the policy perspective : understanding how legal frameworks influence environmental problem solving - McGuire, Chad J. (CRC Press, 2014)
"Government at the federal, state, and local levels are currently moving holistically in a direction where officials are taking on a more direct (regulatory) role in environmental issues. Responding to this trend, this text presents a defining overview of the environment in terms of practical regulation and management, who the players are, and how the law factors in. It details types of law (common, statutory, regulatory) and frameworks (legislative, executive, and judicial) as relevant to environmental issues. The book concludes with coverage of policies and acts by application type (pollution, land use, waste, energy)"-- Provided by publisher.
Keywords: Environmental policy -- United States.; Environmental law -- United States.; elektronické knihy; electronic books